O boato sob o foco linguístico-discursivo filtrado por lentes bakhtinianas - Borges, Sandra Mara Azevedo (2010)
Rumor is an activity of language, which is present in people‟s daily lives, regardless of country, culture, socio-economic and political regime, or time. It is likely to exist in any group of people. Being an object of study in various fields of knowledge such as anthropology, psychology, history, sociology, communication, it seemed appropriate to research it within a linguistic-discursive view. This research relies mostly on Mikhail Bakhtin‟s Philosophy of Language maily considering the following reflections made by the Russian master: dialogism, otherness, text/utterance (Fr. énoncé), audience, context, theme and meaning, meaning construction, discursive genres, among others. Also the category of will to truth brought about by Michel Foucault, as well as specific contributions from various authors on rumor were taken in this study to investigate the following aspects: (a) how this language activity takes place, (b) how such a saying constitutes a speaking subject, (c) what makes a rumor spread and another immediately fade (d) which is its materiality, (e), which differentiates it from a truth and a lie, (f) which causes a rumor to sustain so many official and unofficial actions, so many sayings, (g) how its authoring takes place, (h) how it is constituted, (i) whether the rumor is a speech genre, and if so whether it is a primary or a hybrid genre, (j) if the rumor happens only in oral language, or else, in writing, and also how it takes place (k) how it spreads (l) what its trigger is. These reflections were presented in four chapters, namely: (1) From A Rumor ..., which puts forth the desire to investigate rumor, its theoretical support, and data collection; (2) The Encounter with the Chameleon, which offers, through a dialogue with various researchers, a responsive understanding about the rumor‟s birth and mutation , its spreading, and gaining of credibility; (3) The Chameleon in a Project to Saying, a Will to Truth, which analizes linguistic-discursively three texts that address the Cuban athletes‟ mass desertion rumor during the 2007 Pan American Games, held in Rio de Janeiro; (4) finally, The Chameleon and other animals in the Yellow-Green Country which brings up the use of the term rumor in Brazil and other words of similar meaning such as gossip, hearsay, tittle-tattle, and others. The result of this research has perhaps raised more questions than answers, but it could certainly offer some more understanding about language, the world and the human being.